2018
DOI: 10.1007/978-3-030-02131-3_9
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of Post-quantum Public-Key Cryptography in Smart Mobile Devices

Abstract: The classical public-key schemes are based on number theory, such as integer factorization and discrete logarithm. In 1994, P.W. Shor proposed an algorithm to solve these problems in polynomial time using quantum computers. Recent advancements in quantum computing open the door to the possibility of developing quantum computers sophisticated enough to solve these problems. Post-quantum cryptography (PQC) is resistant against quantum attacks. The aim of this paper is to evaluate the performance of different pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The work developed in ref. [45] uses a Samsung Galaxy A5, model SM-A500H, which is equipped with an Exynos 7880 Octa-core 1.9 GHz processor, to benchmark a range of PQAs, including Classic McEliece [45], again showing extensive keygeneration times compared to the other KEM PQAs, listed with no SSF comparison in this case. No previous studies support the extended SSF decapsulation time that we observed.…”
Section: Comparison With Other Kem Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The work developed in ref. [45] uses a Samsung Galaxy A5, model SM-A500H, which is equipped with an Exynos 7880 Octa-core 1.9 GHz processor, to benchmark a range of PQAs, including Classic McEliece [45], again showing extensive keygeneration times compared to the other KEM PQAs, listed with no SSF comparison in this case. No previous studies support the extended SSF decapsulation time that we observed.…”
Section: Comparison With Other Kem Workmentioning
confidence: 99%
“…For this reason, there is the need to ask the question: how do the selected PQAs perform relative to each other on constrained devices and compared to higher-powered devices? • RQ2: There are numerous groups within the cryptographic community that have tested the performance of PQAs on a range of constrained devices and lower power processors [41,[45][46][47][48]. Whilst the data may not be directly comparable, it would be useful to have supporting data to either confirm or refute the findings of RQ1, and, therefore, we should ask: how do the data from this study compare to those from similar previous studies?…”
mentioning
confidence: 95%